Endoscopic diagnosis and treatment of duodenal neuroendocrine tumours: the experience of the P.A. Hertsen Moscow Oncology Research Institute - V. I. Ryabtseva; S. S. Pirogov; I. B. Perfiliev; D. G. Sukhin; M. A. Paronian; G. F. Minibaeva; N. S. Goeva; N. N. Volchenko (Сибирский онкологический журнал, 2025)
The aim of the study was to analyze the results of endoscopic diagnosis and treatment of patients with duodenal neuroendocrine tumors. Material and Methods. From 2012 to 2024, 20 patients diagnosed with duodenal neuroendocrine tumors were examined, and some of them were treated at the Endoscopy Department of P.A. Herzen Moscow Oncology Research Institute. The median age of the patients was 61 years. Tumors were assessed by the following parameters: location, size, pit and vascular pattern, presence of subepithelial vessels, endosonographic structure, depth of invasion, tumor grade, and the type of treatment. Results. The mean tumor size was 8 ± 5.6 mm [95 % CI: 5.4–10.6]. The duodenal bulb was the most common tumor location (87 %) [95 % CI: 69–100 %]. Only in 13 % of cases, tumor was located in the ascending part of the duodenum [95 % CI: 0–30 %]. In the duodenal bulb, tumors were located on its anterior wall in 70 % of cases [95 % CI: 49–90 %], on the medial wall in 18 % of cases [95 % CI: 2–37 %], and on the posterior wall in 12 % of cases [95 % CI: 0–23 %]. Narrow-band imaging endoscopy revealed that 45 % of tumors had an irregular pit pattern and vascular pattern [95 % CI: 23–66 %], and 30 % of tumors consisted of dilated tortuous subepithelial vessels [95 % CI: 9–50 %]. Endoscopic ultrasonography was used to determine the depth of tumor invasion. In most cases, tumors were localized within the second layer corresponding to the muscular plate of the mucosa. Some patients underwent radical endoscopic treatment (EMR and ESD). Conclusion. In our retrospective analysis of clinical cases, we have identified some trends that are consistent with results of other large studies. Endocopic resection is safe and effective treatment option for duodenal neuroendocrine tumors with no evidence of muscle layer invasion and regional and distant metastases.